EVALUATION OF FORMULATED HERBAL LOZENGES OF PAVETTA CRASSIPES AND ANOGEISSUS LEIOCARPUS LEAF EXTRACTS FOR TREATMENT OF COUGH (Nigerian Journal of Pharmaceutical Research, 2025)
Background: Medicinal plants are a vital healthcare component, particularly in regions where access to conventional medicine is limited. The study aims is to formulate lozenges containing dried hydro-alcohol extracts of leaves of Pavetta crassipes and Anogeissus leiocarpus and evaluate their physico-mechanical properties, antimicrobial efficacy and cough-suppressing ability in laboratory mice.Methods: Hydro-alcoholic extracts of the plants were evaluated for their pharmacological efficacy using ammonia-induced cough model in albino mice, antimicrobial susceptibility testing against selected microorganism and acute toxicity. Four batches of hard lozenges containing 0 % extract, 10 % of either extract and combination of both extracts at 5 % each were prepared and labelled L1, L2, L3, L4 respectively. The lozenges were evaluated for physico-mechanical properties. Pharmacological efficacy of the lozenges in cough suppression was determined in albino mice. Antimicrobial susceptibility of the lozenges was also evaluated against selected micro-organisms.Results: The lozenges had characteristic odor, sticky texture, and moderately sweet to moderately bitter taste. All the batches had uniform weights ranging between 1.43 and 1.68 g, hardness was between 15.98 and 25.24 kgF and friability was < 1 %. Moisture content was low (0.79 and 1.10 %) and dissolution time was between 9- and 11-min. Antimicrobial susceptibility was more significant with formulations L2 and L4 while cough suppression effect was most significant with L4 (88.61 %).Conclusion: This study presents a promising natural alternative for management of cough, potentially reducing the heavy reliance on synthetic drugs and offering a sustainable, culturally integrated approach to healthcare.